Evaluasi dan Analisis Kualitas dan Kualitas Udara pada Terowongan Lubang Japang di Kota Bukittinggi - Teddi Triandana; Bambang Heriyadi (Journals Mining Engineering : Bina Tambang, 2018)
Abstract. Lubang Japang is an ancient tunnel that build during Japanesse’s colonizing in Indonesia. However it refuctioned after Indonesian Independency and officially became tourist area at 1984. Known as a tourist destination in Bukittinggi, Lubang Japang tunnel has excalation amount of visitors yearly. Tunnel has the limitation amount and quality of circulated air in it. There are range borders such as determinations of Kepmen 555.K/26/M.P.E/1995 that organizing air quality and quantity in the tunnel for circulationing process. Then the analysis between air quality and quantity in tunnel and range borders to satisfy the requirment of fresh air for visitor is needed. Base on range borders of Kepmen 555.K/26/M.P.E/1995 in point 2 to point 11 at certain time and weather terms have percentage of humidities below the mark along with point 9 that has the lowest effective temperature in 16,85%. Meanwhile the gas contents (O2 dan CO2) of all locations in Lubang Japang tunnel are safe and up to standard. So by the comparison between current air circulation’s debit and respiration requirment per-second based on Kepmen 555.K/26/M.P.E/1995 known that the maximum of visitors are 398 persons periodically, yet amount of visitors are down to 196 persons while puoring rain. Then the result of air usage evaluation for visitor at the moment is fulfilled.Keywords:  air quantity, temperature, air circulation, tunnel, range border